2020
DOI: 10.22541/au.160794364.42389606/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Roles of leaf trichomes in heat transfers and gas‐exchange characteristics across environmental gradients

Abstract: Dense leaf trichomes can directly decrease gas fluxes through increased gas diffusion resistance and indirectly increase gas fluxes through increased leaf temperature due to increased heat diffusion resistance, which may contribute to adaptation to dry and/or low‐temperature conditions. However, it remains unclear whether the leaf‐trichome resistance increases or decreases the gas‐exchange rates through combined direct and indirect effects. We focused on Metrosideros polymorpha, a dominant tree species inhabit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Meinzer and Goldstein (1985) simulated effects of hairs on energy balance in Espletia timotensis by assuming hairs entrained a layer of still air equal to their depth and that hairs did not affect absorptance; their simulations reasonably matched observations of greater leaf temperatures in hairy as compared to partially-shaved leaves. Amada et al (2021) observed lower in situ leaf temperatures in shaved versus hairy leaves of Metrosideros polymorpha ; having verified that surface conductances to water vapor did not differ between the two treatments, the authors attributed the result to reduction in g bh , and thus in convective cooling. That result could also have arisen from effects of leaf hairs on radiation absorption, although hairs in M. polymorpha are light in color and thus probably reduced radiation absorption rather than the converse.…”
Section: Discussionmentioning
confidence: 90%
“…Meinzer and Goldstein (1985) simulated effects of hairs on energy balance in Espletia timotensis by assuming hairs entrained a layer of still air equal to their depth and that hairs did not affect absorptance; their simulations reasonably matched observations of greater leaf temperatures in hairy as compared to partially-shaved leaves. Amada et al (2021) observed lower in situ leaf temperatures in shaved versus hairy leaves of Metrosideros polymorpha ; having verified that surface conductances to water vapor did not differ between the two treatments, the authors attributed the result to reduction in g bh , and thus in convective cooling. That result could also have arisen from effects of leaf hairs on radiation absorption, although hairs in M. polymorpha are light in color and thus probably reduced radiation absorption rather than the converse.…”
Section: Discussionmentioning
confidence: 90%
“…At high temperatures, the trichomes increase because they function to prevent excessive evaporation of the leaves. This condition is mainly Increasing leaf temperature affects trichomes, which can increase the activity of photosynthetic enzymes; leaf trichomes can increase the rate of photosynthesis (Amada et al, 2020). The flavonoid content is expressed in mg 100 g -1 dry matter.…”
Section: Resultsmentioning
confidence: 99%
“…However, other studies found drought stress did not induce trichome production (Piritta et al 2010). Furthermore, the formation and development of trichomes can be significantly influenced by temperature (Skelton et al 2012, Amada et al 2020). However, it remains unclear exactly which environmental factors primarily drive spatial variations in leaf trichome densities.…”
Section: Introductionmentioning
confidence: 99%